Design, Synthesis, and Biological Activity of Novel Chalcone Derivatives Containing an 1,2,4-Oxadiazole Moiety - Luo, Ling; Liu, Dan; Lan, Shichao; Gan, Xiuhai (Frontiers in Chemistry, 2022)
To discover the lead compound for agricultural use, thirty-four novel chalcone derivatives containing an 1,2,4-oxadiazole moiety were designed and synthesized. Their nematocidal activities against Bursaphelenchus xylophilus, Aphelenchoides besseyi, and Ditylenchus dipsaci and their antiviral activities against tobacco mosaic virus (TMV), pepper mild mottle virus (PMMoV), and tomato spotted wilt virus (TSWV) were evaluated. Biological assay results indicated that compound A13 and A14 showed good nematocidal activities against B. xylophilus, A. besseyi, and D. dipsaci, with the LC50 values of 35.5, 44.7, 30.2 μg/mL and 31.8, 47.4, 36.5 μg/mL respectively, which were better than tioxazafen, fosthiazate, and abamectin. Furthermore, compounds A16 demonstrated excellent protective activity against TMV, PMMoV and TSWV, with the EC50 values of 210.4, 156.2, and 178.2 μg/mL, respectively, which were superior to ningnanmycin (242.6, 218.4, and 180.5 μg/mL).